Conversion Rate and Feed Efficiency of Silver Pompano Fish (Trachinotus blochii) With Different Frequency Giving - Ibrahim Saputra; Tri Yulianto (Journal of Aquaculture Science, 2018)
The value of conversion rate and feed efficiency is a parameter for determining the quality, treatment, or feed given to the growth of Silver Pompano (Trachinotus blochii). The purpose of this study was to determine the effect of feeding frequency on feed conversion and efficiency and survival of Silver Pompano. The research method used was a Completely Randomized Design (RAL) with 3 treatments (Control namely feeding once a day, A was feeding 2 days, and B was feeding once every 3 days) with 3 replications. The best results were K treatment at 2.11 g (feed conversion ratio), 47.32% (feed efficiency), and 100% (survival). The conclusion of this study is that the treatment given during the study by ANOVA analysis did not give a significant effect on the conversion value and feed efficiency. Feeding with a frequency of 1 time a day (control) shows the best weight growth and can be applied to cultivation.   Keywords: conversion rate, feed efficiency, Silver Pompano